An epidemiological study of pleuropulmonary paragonimiasis among pupils in the peri-urban zone of Kumba town, Meme Division, Cameroon - Kefie-Arrey Charles; Moyou-Somo Roger; Dreyfuss Georges; Dumas Michel (BMC, 2003)
Abstract Background Paragonimiasis have previously been reported in two zones of the Southwest Province of Cameroon including the Kupe mountain and Mundani foci. The aim of this study was to investigate the presence and epidemiology of paragonimiasis in the peri-urban zone of Kumba, Meme Division, located about 50 km away from the Kupe mountain focus. Methods Pupils of several government primary schools in 5 villages around Kumba underwent both parasitologic and clinical investigations in search of signs and symptoms of paragonimiasis. Mycobacterium tuberculosis was also searched for in the differential diagnosis.Freshwater crabs from neighbouring streams in the five villages were dissected in search of paragonimus metacercariae. Results Out of a total of 1482 pupils examined in all five villages, 309 individuals (147 males and 162 females) were recruited for this study based on the presence of one or more signs or symptoms of paragonimiasis. Eggs of Paragonimus africanus were found in stools and/or sputum of pupils from all five villages, giving an overall paragonimus prevalence of 2.56%. There was no significant difference in the disease prevalence between the villages (X2 = 8.36, P = 0.08). The prevalence of Paragonimus africanus eggs amongst pupils with symptoms of paragonimiasis was 12.3% (38 of 309). Males were infected more than females (17.0% versus 8.0%), but the difference was not significant (X2 = 5.76, P = 0.16). All the 38 paragonimus egg positive subjects presented with cough, 23 (60.53%) complained of chest pain while 16 (42.11%) had haemoptysis. Stool examinations also detected some intestinal parasites including Ascaris lumbricoides (29.45%), Trichuris trichiura (6.47%), Necator americanus (2.27%), Strongyloides stercoralis (1.62%), Enterobius vermicularis (0.65%), and Entamoeba histolytica (4.53%). No case of M. tuberculosis was noted. Out of a total of 85 dissected crabs (Sudanonautes africanus), 6.02 % were infected with paragonimus metacercariae. Conclusion In addition to the two previously described paragonimiasis foci of Kupe mountain and Mundani, the identification of autochthonous cases of paragonimiasis in the peri-urban zone of Kumba town, makes the South West Province the most endemic zone of paragonimiasis in Cameroon at present.